THEORETICAL BASICS OF STUDYING THE TOURIST POTENTIAL OF THE CULTURAL AND ARTISTIC PHENOMENON OF THE UKRAINIAN BAROQUE - DARCHYK, Maksym (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. Ukrainian Baroque is an important cultural and artistic phenomenon for Ukraine and has significant tourist potential, which is relevant in the context of growing interest in Ukrainian culture. The latest research and publications were analyzed and an insufficient level of study of the topic of such a narrow issue was revealed, but the topic was widely disclosed at the level of individual aspects. The purpose of the study was to reveal the cultural and artistic phenomenon as a resource for tourism development using the example of the Ukrainian Baroque. Methods. The methods of analysis, SWOT analysis, induction, historical and generalization were used. Results. The concepts of culture, art, cultural and artistic phenomenon, cultural tourism, tourist potential, baroque, Ukrainian (Cossack, Mazepa) baroque and the definition of the phenomenon were revealed. During the study, the author’s definitions of tourist potential and tourist potential of a cultural and artistic phenomenon were determined and proposed. A SWOT analysis of the tourism potential of cultural and artistic phenomena was conducted. Conclusions. The theoretical foundations of tourism research of the tourism potential of cultural and artistic phenomenon were investigated and revealed. In particular, the Ukrainian Baroque was considered as a phenomenon that combines European Baroque trends with Ukrainian traditions. According to the results of the study, specific sequential steps were proposed to determine the directions of development of the tourism potential of cultural and artistic phenomena. Research directions were proposed to determine the possibility of using the phenomenon of Ukrainian Baroque in tourism.